2021
DOI: 10.1002/icd.2243
|View full text |Cite
|
Sign up to set email alerts
|

Fine motor abilities and parental input of spatial features predict object word comprehension of Turkish‐learning children

Abstract: Object word learning can be based on infant‐related factors such as their manual actions and socio‐linguistic factors such as parental input. Specific input for spatial features (i.e., size, shape, features of objects) can be related to object word comprehension in early vocabulary development. In a longitudinal study, we investigated whether fine motor abilities at 14 months and parental input for spatial features at 19 months predicted object word comprehension at 25 months. Twenty‐seven Turkish‐learning chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Fine motor skills refer to the performance of manual actions like grasping, rolling, throwing, reaching, pinching by smaller muscles, hands, and fingers [1,2,21]. The development of these skills starts early on and continues through adolescence [1,5].…”
Section: Related Work 21 Fine Motor Development In Childrenmentioning
confidence: 99%
See 3 more Smart Citations
“…Fine motor skills refer to the performance of manual actions like grasping, rolling, throwing, reaching, pinching by smaller muscles, hands, and fingers [1,2,21]. The development of these skills starts early on and continues through adolescence [1,5].…”
Section: Related Work 21 Fine Motor Development In Childrenmentioning
confidence: 99%
“…Therefore, this age period is critical for supporting fine motor skills of young children [7]. Fine motor skills play a crucial role in children's daily activities such as dressing, eating, drawing, and self-care (e.g., [5,6,25]) Early fine motor skills are also related to children's cognitive and language skills (e.g., [17,21,33]). For example, exploring objects manually is associated with infants' word learning [33].…”
Section: Related Work 21 Fine Motor Development In Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…Webster et al (2006) have shown that motor skill deficits and language deficits often coincide. Furthermore, various studies have found links between Fine Motor Skills (FMS) and different language outcomes (Houwen et al, 2016; Kobaş et al, 2021; Muluk et al, 2014; Suggate & Stoeger, 2014; see Gonzalez et al, 2019 for an overview) and that speech production (Tokimura et al, 1996) and language perception (Flöel et al, 2003) activate the hand area of the motor cortex.…”
mentioning
confidence: 99%